İbnü’l- Hümam’ın Fethu’l- Kadir’de hadis usulü meselelerine yaklaşımı - Özüdoğru, Bekir (My University, 2008)
İBNÜ'L-HÜMÂM'IN FETHU'L-KADÎR'DE HADİS USÛLÜ MESELELERİNE YAKLAŞIMI ÖZET İslam dininin ikinci kaynağı olan sünnetin gerek tespiti gerek doğru anlaşılması gerekse delil oluşu yönünde birçok eser telif edilmiştir. Bir Hanefî fakîhi olan İbnü’l-Hümâm, mezhebin önemli furû’-ı fıkıh kaynaklarından el-Hidâye’yi şerh ettiği Fethu’l-kadîr’de, fıkıh konularının yanında, delil alınan hadisleri sened ve metin açısından geniş bir biçimde değerlendirerek furû’-ı fıkıh eserlerinde az rastlanılan bir metot izlemiştir. Bu çalışmada İbnü’l-Hümâm’ın Fethu’l-kadîr adlı eseri esas alınarak onun sünnet anlayışı, hadisçiliği, merfû’, mevkûf hadis, seneddeki kopukluk (mürsel, müdelles, munkatı’ hadis), râvi değerlendirmeleri, metin tenkidi ve ihtilâfü’l-hadis gibi bazı hadis usûlu meselelerine yaklaşımı ortaya konulmaya çalışılmıştır. IBNU’L HUMAM’S APPROACH TO THE ISSUES OF HADITH METHODOLOGY IN HIS FATHU’L QADIR

There are lots of works to be authored to fix the sunnah as the second source of Islam and to understand it rightly. Ibnu’l-Humam as an Hanafiti scholar, wrote a commentary on al-Hidaya, one of the most important sources of Islamic Jurisprudence, in his Fathu’l Qadir. In His Fathu’l Qadir, he followed a methodology used rarely in the books of Islamic Jurisprudence so that widely analysed Hadiths taken as evidence from the perspective of narration and text. In this study, Ibnu’l-Humam’s approach to some issues of Hadith Methodology such as his understanding of sunnah, his hadith scholarship, marfu’ and mawquf hadiths, the problem of transmission, evaluating narrators, criticising text and differences in hadiths have been studied by taking Ibnu’l Humam’s Fathu’l-Qadir as basic.
Keywords: Hadis; İslam Dini